1996
DOI: 10.1007/s004010050542
|View full text |Cite
|
Sign up to set email alerts
|

Preferential expression of Fas/APO1 (CD95) and apoptotic cell death in perinecrotic cells of glioblastoma multiforme

Abstract: Fas/APO-1 (CD95)-mediated apoptosis is one of the major mechanisms of programmed cell death. We have previously shown by reverse transcriptase-polymerase chain reaction that Fas is frequently expressed in malignant gliomas [Tachibana et al. (1995) Cancer Res 55: 5528-5530]. In this study, we assessed Fas expression in astrocytomas using a polyclonal anti-Fas antibody. Immunoreactivity to Fas was detected in 1 out of 9 (11%) low-grade astrocytomas (WHO grade II), 2 of 11 (18%) anaplastic astrocytomas (WHO grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 27 publications
1
27
1
1
Order By: Relevance
“…In astrocytic tumors, the incidence of apoptotic cell death in situ has been shown to correlate with tumor grade, with the proportion of cells undergoing apoptosis being greater in anaplastic astrocytomas and GBMs than in lower-grade astrocytomas (Kordek et al, 1996). Apoptosis also occurs more frequently in GBM cells within perinecrotic areas (Kordek et al, 1996;Tachibana et al, 1996). Further, Yin et al (1999) have observed that Cdk5 protein and kinase activity were increased in human head and neck squamous cell carcinoma xenografts undergoing spontaneous apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In astrocytic tumors, the incidence of apoptotic cell death in situ has been shown to correlate with tumor grade, with the proportion of cells undergoing apoptosis being greater in anaplastic astrocytomas and GBMs than in lower-grade astrocytomas (Kordek et al, 1996). Apoptosis also occurs more frequently in GBM cells within perinecrotic areas (Kordek et al, 1996;Tachibana et al, 1996). Further, Yin et al (1999) have observed that Cdk5 protein and kinase activity were increased in human head and neck squamous cell carcinoma xenografts undergoing spontaneous apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated by Trizol Reagent (GIBCO͞BRL). The first strand of cDNA was synthesized with oligo(dT) primers and Moloney murine leukemia virus reverse transcriptase (GIBCO͞BRL) (19). PCR amplification was performed with Fas primers (5Ј-CACTATTGCTGGAGTCATG-3Ј and 5ЈCTGAGTCACT-AGTAATGTCC-3Ј) or ␤-actin primers (5Ј-CATCCTCAC-CCTGA AGTACC-3Ј and 5Ј-GGTGAGGATCT TCAT-GAGGT-3Ј) for 30 cycles at 94°C for 15 sec, 60°C for 30 sec, 72°C for 1 min, and 72°C for 5 min using AmpliTaq DNA polymerase and the 9600 GeneAmp PCR system (PerkinElmer).…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Most Fas expression in GBM is within pseudopalisades corresponding to their higher levels of apoptosis. 22,23 Contact between tumor cells expressing FasL and those expressing Fas may facilitate apoptosis. 24 Overall, however, levels of apoptosis are generally low in malignant gliomas; apoptosis accounts for a slim minority of cell death; and apoptotic rates do not correlate with prognosis.…”
Section: Necrogenesis In Gbmmentioning
confidence: 99%